Laboratory-Scale Testing of a Solar Panel-Based Portable Power Bank Design - Adrix Richard Stanlee; Fahmy Rinanda Saputri; Ricardo Linelson (Universitas Islam Raden Rahmat, Malang, 2024)
The increasing need for mobile device charging, especially in outdoor and remote areas, presents challenges due to limited access to power sources. This issue is particularly relevant for individuals who travel frequently, such as motorcycle taxi drivers. To address this issue, a foldable solar panel-based portable power bank has been developed, which is designed to efficiently convert solar energy into electrical power to charge smartphones. Laboratory-scale tests show that the device can charge a smartphone from 20% to 100% within four hours under peak sunlight conditions, and from 20% to 75% under lower sunlight. To further improve its usability, future development should increase the energy storage capacity, improve efficiency under different sunlight conditions, add weather resistance, and expand compatibility with other devices, making it more suitable for outdoor and travel applications.